71.6k views
3 votes
What is the solution of (2/x-1)>(7/x+1)

1 Answer

5 votes

Answer:

Given inequality,


(2)/(x) - 1 > (7)/(x) + 1

Using the property a > b ⇒ a + c > b + c ∀ a, b, c ∈ R


(2)/(x) > (7)/(x)+2

Using the property a > b ⇒ a - c > b - c ∀ a, b, c ∈ R


(2)/(x)-(7)/(x) > 2


(2-7)/(x) > 2


-(5)/(x) > 2

Case 1 : If x > 0 ⇒ -x < 0

∵ a > b ⇒ ca < cb if c < 0,


\implies 5 < -2x

Now, -1/2 < 0


\implies -(5)/(2) > x

Case 2 : If x < 0 ⇒ -x > 0

∵ a > b ⇒ ca > cb if c > 0,


\implies 5 > -2x

Now, -1/2 < 0


\implies -(5)/(2) < x

User Pillowcase
by
5.5k points